A sensitive, reproducible and flexible treadmill test for predicting 10 km running performance in trained runners - Read, B.; Weston, A. R. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Whilst VO2max is a good predictor of endurance performance in a heterogenous group, it has proved insensitive in a more homogenous well-trained group. Furthermore it requires expensive gas analysis equipment. Other tests require either maximal efforts or invasive procedures. In the current study, the ability of a variety of measurement outcomes obtained from a new four stage treadmill protocol, to reproducibly predict 10 km running performance was investigated. Ten competitive male 10 km runners (31:40 - 39:00 min:sec) were tested on three occasions. The protocol consisted of three 5 min workloads (14, 16, 18 km/hr) each followed by 1 min rest, followed by a fourth workload (20 km/hr) to fatigue. HR, VO2, RER, plasma La were measured at each workload and total running time to fatigue (TTF) was recorded. Measurements were compared to current 10 km race time and reproducibility was assessed between the second and third trial. When considering measurement outcomes from the third trial, several showed a good correlation with 10 km race time: TTF r = -0.92, p < 1; La18km/hr r = 0.94, p < 0.001; RER18km/hr r = 0.72, p < 0.05. Results obtained on the second trial were typically also significantly, but less strongly, correlated. Regression analysis showed both TTF and plasma lactate at 18 km/hr (La18) were good predictors of 10 km race time: 10 km time = -0.529 TTF (min) + 45.355, r = 0.92 10 km time = 0.706 La18 (mmol/l) + 30.089, r = 0.94 Neither regression equation was strengthened by the addition of other measurement outcomes. Both TTF and La18 were reproducible with intraclass correlations of r=0.97 (95%CI 0.88-0.99) and 0.95 (95%CI 0.79-0.99) respectively. In conclusion, this protocol is reproducible and can provide a good prediction of 10 km race performance from submaximal plasma lactate measures without gas analysis or maximal efforts. Alternatively invasive procedures can be avoided by measuring time to fatigue alone.